2022
DOI: 10.51544/jmn.v5i1.2424
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Progressive Muscle Relaxation (Pmr) on Blood Glucose Levels With Diabetics

Abstract: One of the efforts that must be do with Diabetes Mellitus to keepsstable blood sugar is physical exercise. PMR can lower blood sugar, the patients Diabetes Mellitus causing a relaxed state. The purpose of the study was to determine effectiveness of PMR on reducing levelsglucose blood with diabetes using a Quasi Experiment With Control Group design. The sample of this study was patients with Diabetes Mellitus in the working area of the Banda Raya Health Center Banda Aceh as many as 54 people who were selected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…This aligns with several studies on progressive muscle relaxation on blood glucose levels (Akbar et al, 2018;Isnaini et al, 2017;Rufaida et al, 2018;Sitio et al, 2022). The results showed that providing progressive muscle relaxation reduced blood sugar levels in diabetes mellitus sufferers.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…This aligns with several studies on progressive muscle relaxation on blood glucose levels (Akbar et al, 2018;Isnaini et al, 2017;Rufaida et al, 2018;Sitio et al, 2022). The results showed that providing progressive muscle relaxation reduced blood sugar levels in diabetes mellitus sufferers.…”
Section: Introductionsupporting
confidence: 90%
“…Based on the results of the research above it is in line with research conducted by (Martuti et al, 2021) Regarding the application of progressive muscle relaxation to the blood sugar levels of type 2 diabetes mellitus patients in the working area of the Metro Health Center; the results showed that there was a decrease in blood sugar levels in diabetes mellitus patients before and after the intervention. Apart from that, several studies are based on the research above that have been carried out by (Akbar et al, 2018Isnaini et al, 2017Rufaida et al, 2018;Sitio et al, 2022). The effect of progressive muscle relaxation on blood sugar levels shows a significant reduction in giving progressive muscle relaxation to blood sugar levels in diabetes mellitus sufferers.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil penelitian ini didapatkan kadar Gula Darah menunjukkan penurunan yang signifikan sebesar 10,46 mg/dl pada kelompok yang diberikan intervensi relaksasi otot progresif dibanding kelompok kontrol yang hanya berefek menurunkan kadar gula darah sebesar 6 mg/dl. Hasil penelitian ini sejalan dengan penelitian Sitio et al, (2022) yang menunjukkan penurunan nilai rata-rata kadar gula darah yang lebih besar (55,63) pada kelompok yang diberikan relaksasi otot progresif dibanding kelompok kontrol (3,22).…”
Section: Pembahasanunclassified